Stereoselective Construction of Vicinal Quaternary Stereocenters via the 1,6-Conjugate Addition of β,β-Disubstituted N-Sulfinyl Metalloenamines to Isatin-Derived para-Quinone Methides - Li, Zheng-Fei; Lu, Chong-Dao (Synthesis, 2024)
A 1,6-conjugate addition reaction of β,β-disubstituted N-tert-butanesulfinyl metalloenamines, generated via stereospecific α-deprotonation of enantioenriched α,α-disubstituted ketimines or deprotonation of the NH in geometry-defined enesulfinamides, with isatin-derived para-quinone methides is developed to build vicinal quaternary stereocenters with high stereocontrol. The resulting 3,3-disubstituted oxindoles contain a less-accessible acyclic quaternary stereogenic carbon substituted with two sterically and electronically similar groups at the α-position of the imino group. This protocol constitutes a rare example of the stereoselective construction of vicinal quaternary stereocenters via the conjugate addition of acyclic enolates/aza-enolates bearing two similar β-substituents.
Keywords: N-sulfinyl metalloenamines; conjugate addition; deprotonation; quaternary stereocenter; stereoselectivity